C/EBPβ Regulates Tumour Size and Microenvironment Composition in Lewis Lung Carcinoma - Saleh, Aisha (Université d'Ottawa | University of Ottawa, 2026)
CCAAT/enhancer-binding protein beta (C/EBPβ) is a critical transcription factor involved in cellular differentiation, inflammation, and metabolic regulation. Although C/EBPβ has been implicated in both oncogenic and tumour-suppressive functions across different cancer types, its role in lung cancer, particularly in the widely used Lewis lung carcinoma (LLC) model, remains poorly defined. The objective of this study was to define the role of C/EBPβ in LLC tumour progression and to characterize how C/EBPβ shapes the tumour microenvironment. Bulk RNA-seq of Lewis lung carcinoma (LLC) and MC38 colon carcinoma cells grown as adherent monolayers or hanging-drop spheroids revealed a conserved “core spheroid signature” of 1, 527 genes, characterized by enrichment of autophagy-related pathways and suppression of cell-cycle programs. Consistent with this, spheroids exhibited an increase of cells in G0/G1, indicating an enrichment of cellular quiescence. Within shared spheroid-induced transcription factors, Cebpb was significantly upregulated in both models, and immunoblotting confirmed increased C/EBPβ protein driven by elevation of the LAP isoform. Functionally, CRISPR-mediated C/EBPβ knockout impaired 3D tumour growth: spheroids were smaller while only modest changes to cell-cycle distribution, suggesting that C/EBPβ supports efficient expansion in 3D environments through mechanisms beyond cell-cycle modulation. Consistent with a spheroid-associated ER-stress adaptation program, Hspa5 (encoding the ER-stress chaperone BiP) was upregulated in both spheroid models; however, only in LLC did C/EBPβ loss reduce BiP levels and impair survival under endoplasmic reticulum (ER) stress. We next focused on the LLC model using complementary loss- and gain-of-function strategies: a CRISPR-mediated Cebpb knockout cells and C/EBPβ-overexpressing cells. We found that C/EBPβ knockout reduced tumour size while C/EBPβ overexpression increased it. Transcriptomic profiling of these models revealed two major C/EBPβ-associated programs. One comprised immune-related pathways, with gene sets linked to leukocyte migration/chemotaxis and immune signaling downregulated in the C/EBPβ knockout and upregulated with C/EBPβ overexpression. Flow-cytometry of immune population found NK cell proportions increased with C/EBPβ knockout and decreased with overexpression, while macrophage abundance shifted in the opposite direction, with an increase in M2-like macrophages at early timepoints in the overexpression model. The second transcriptomic program identified was angiogenesis that was bidirectionally regulated: angiogenesis-related genes and pathways were downregulated in C/EBPβ knockout cells and upregulated with C/EBPβ overexpression. C/EBPβ promoted angiogenesis in vitro and in vivo: increased CD31⁺ vascular density, and bidirectionally regulating an angiogenesis gene set. Ligand-receptor annotation and integration with single-cell receptor landscapes further indicated that C/EBPβ predominantly amplifies secreted signaling programs, including cues linked to NK-associated, myeloid and endothelial interactions. Having established C/EBPβ as a driver of tumour growth and microenvironmental programs in LLC, we screened FDA-approved compounds for pharmacologic down-regulators of C/EBPβ. Zileuton was identified as a candidate pharmacologic down-regulator of C/EBPβ. In vivo, treatment of established LLC tumours with zileuton for two weeks reduced tumour weight relative to vehicle controls. Cytokine profiling further showed downregulation of cytokines, including a decrease in CCL2. Notably, CCL2 was also a C/EBPβ-regulated gene in our genetic models, decreasing with C/EBPβ knockout and increasing with C/EBPβ overexpression, aligning zileuton-associated cytokine modulation with the C/EBPβ-regulated transcriptional program. Together, these data fill a gap by systematically defining C/EBPβ function in the widely used LLC lung cancer model. C/EBPβ emerged as a shared 3D-responsive transcription factor whose induction is shared across tumour models, and whose modulation in LLC reveals roles in tumour growth, immune composition, and angiogenesis, with zileuton identified as a candidate pharmacologic strategy to target this axis.
Keywords: C/EBPβ tumour microenvironment; Lewis lung carcinoma (LLC); tumour microenvironment; angigoensis; immune regulation; spheriod; quiescence; zileuton